Efficiency, quality of forecasts and Radner equilibria - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2020)
We study a simple two period economy with no uncertainty and complete markets where agents trade based on forecasts about the second period spot price. We propose as our solution concept a set of forecasts with the following properties: there exist (heterogenous) forecasts contained in this set that lead to efficient allocations, the set contains only those forecasts that correspond to some efficient equilibrium, and Önally that the forecasts assign positive probability to the actual market clearing spot price. We call such a set of prices an efficient equilibrium with ambiguity, and interpret it as a generalization of Radner equilibrium that delivers efficient allocations under forecasts that possess a self-fullling property that is weaker than perfect foresight.